Well-Child Care Clinical Practice Redesign at a Community Health Center - Kelly Mooney; Candice Moreno; Paul J. Chung; Jacinta Elijah; Tumaini R. Coker (SAGE Publishing, 2014)
Background: Community health centers (CHCs) are a key element of the health care safety net for underserved children. They may be an ideal setting to create well-child care (WCC) clinical practice redesign to drastically improve WCC delivery. Objective: To examine the perspectives of clinical and administrative staff at a large, multisite urban CHC on alternative ways to deliver WCC services for low-income children aged 0 to 3 years. Methods: Eight semistructured interviews were conducted with 4 pediatric teams (each consisting of 1 pediatrician and 2 medical assistants) and 4 CHC executive/administrative staff (Medical Director, COO, CEO, and Nurse Supervisor). Discussions were recorded, transcribed, and analyzed using the constant comparative method of qualitative analysis. Salient themes included WCC delivery challenges and endorsed WCC clinical practice redesign solutions. Results: The 3 main WCC delivery challenges included long wait times due to insurance verification and intake paperwork, lack of time for parent education and sick visits due to WCC visit volume, and absence of a system to encourage physicians to use non-face-to-face communication with parents. To address WCC delivery challenges, CHC providers and administrators endorsed several options for clinical practice redesign in their setting. These included use of a health educator in a team-based model of care, a previsit tool for screening and surveillance, Web site health education, a structured system for non-face-to-face (eg, phone) parent communication, and group visits. Conclusion: CHC-specific strategies for WCC clinical practice redesign endorsed by a large, multisite safety net clinic may lead to more efficient, effective, and family-centered WCC for low-income populations.